Do informador de polícia ao agente provocador - Gíria, João Filipe de Oliveira Coelho (2017)
The production of evidence is the central object of criminal investigation. Finding out the existence of a crime and determining its agents, allowing the discovery of the truth, prosecution of the guilty and the acquittal of the innocent is the basis for investigation of any wrongdoing. The reconstitution of a fact is not always intelligible, so investigators must take into account all versions that arise on the criminal scenario. They should take into account that in addition to their investigation training, there are people who get information about a reality that is sometimes only possible to reach with their testimony. The use of this gathered information can be a key catalyst for the accountability of perpetrators. However, investigators should be aware of how this information was obtained. The very relationship between the police officer and the human source of information must respect certain principles and rules so that the main subject of the criminal investigation is not accused under deceptive and offensive means against its rights, freedoms and guarantees. In addition to the human sources of information, there are other evidence collection entities that some authors designate as reliable men. They all aim at identifying means and methods that can contribute to the investigation, but the line between legality and illegality is very thin, so there should be restraint on creating criminal scenarios that could compromise the legality of the investigation.